Green technologies and sustainable development : coherent strategies for developing countries - Dana, Léo-Paul; Khanna, Kirti (Emerald Publishing Limited, 2025)
Green Technology and Sustainable Development are essential pillars for addressing the pressing environmental challenges and fostering holistic progress in developing nations. The developing countries are grappling with rapid urbanization, population growth, and resource constraints; adopting green technology practices becomes not only a necessity but also an opportunity to enhance economic stability, improve public health, and reduce their environmental footprint. In developing economies, sustainable development stands as an overarching goal, encompassing economic growth, social equity, and environmental conservation. Achieving this equilibrium requires rethinking traditional approaches and integrating green technology solutions that can mitigate the adverse environmental effects often associated with rapid development. Green technology, characterized by innovation and efficiency, encompasses a wide array of practices and technologies designed to reduce resource consumption, minimize pollution, and promote a harmonious coexistence with nature. Green Technologies and Sustainable Development: Coherent Strategies for Developing Countries is a meticulously curated volume that brings together the expertise and insights of multiple authors, each contributing a unique perspective on the pivotal role of green technologies in advancing sustainable development within the context of developing nations. This collaborative effort results in a comprehensive guide that addresses the multifaceted challenges faced by these countries and offers actionable solutions through green innovation.